A simple design and fabrication of polarization reconfigurable antenna for industrial scientific and medical-band applications - Md. Azad Hossain; Muhammad Asad Rahman; Abu Hena Murshed; Eisuke Nishiyama; Ichihiko Toyoda (Institute of Advanced Engineering and Science, 2023)
This paper proposes a simple microstrip patch antenna (MPA) that can reconfigure its polarization states from linear to circular polarization in real-time by means of a PIN diode. An antenna is fed by a 50 Ω coaxial cable through the substrate of Teflon with relative permittivity of 2.15. The proposed antenna possesses a simple patch with a one-sided corner truncated to achieve polarization reconfigurability. A PIN diode is loaded to connect the main patch with a truncated corner and further maintain dual polarization states such as linear polarization (LP) and circular polarization (CP). Advanced design system (ADS) was used as a simulator to simulate the antenna, and a good understanding was obtained between simulated and measured results. Measured results showed a good agreement with simulated results at all working frequencies of interest. It shows minimum reflection coefficient gain with -10 dB scattering bandwidth 100 MHz for LP states and 170 MHz for CP states. It also shows an axial ratio of 1.56 dB for CP, and the cross-polarization level is also in a satisfying range.